Wishes - Van, Muon (Orchard Books, an imprint of Scholastic Inc., 2021)
"In this spare, poetic picture book based on author Muon Van's family history and told through a series of wishes, a family packs up everything they own and embarks on a perilous oceanic voyage toward a better life"--